Efficacy of fluoride varnish, low-level laser therapy, and the association of therapies in dentin hypersensitivity: a randomized split-mouth clinical trial - Ana Carolina Barbosa Nascimento da Silva; Aline Kataki Paixão; Camilla Magnoni Moretto Nunes; Tainá Ribeiro de Moraes; Leticia Cavassini Torquato; Taciana Marco Ferraz Caneppele; Ivan Balducci; Dimas Renó de Lima; Andrea Carvalho de Marco (Brazilian Dental Science)
Objective: The present study aimed to compare the efficacy of 5% sodium fluoride varnish, LLLT, and the association of fluoride varnish with LLLT in dentin hypersensitivity (DH). Material and Methods: Fifteen patients meet the inclusion criteria. Sixty selected teeth were distributed among the groups through a randomized allocation sequence and received a single application of therapies in the split-mouth scheme: 5% fluoride varnish (F Gr), 780 nm GaAlAs laser (LLLT Gr) - dose of 52.5 J / cm2 (70 mW and 30 seconds) or 2.1 J per point, for 6 seconds in 5 points of application per tooth, the association of both (F + LLLT Gr) and control group (C Gr). The visual analog scale (VAS: 0-10) was used to record dentin hypersensitivity. The results were evaluated at baseline, 24 hours, 30-, 90-, and 180-days periods. The data were analyzed with Friedman and Kruskal-Wallis tests (alpha=0.05) Results: The therapeutic modalities, fluor varnish, low-level laser therapy, and association of both demonstrated significant reduction of DH from baseline to 30-, 90-, and 180-days. Conclusion: The therapeutic modality that was most effective in reducing DH and sustaining the reduction was the association of 5% fluoride varnish with LLLT.